Majalah Azan Sebagai Media Penyebar Pengetahuan Islam di Pattani Thailand - Harfiani, Rizka; Chapakiya, Suraiya (Yayasan Rahmat Islamiyah, 2024)
The spread of Islamic teachings through various strategies and media is carried out in various countries throughout the world. Pattani, which is a province in Thailand, is still trying to maintain Islamic culture, through the spread of Islamic knowledge among the community. One of the efforts made is by publishing Azan magazine, which provides reading related to Islamic knowledge. The characteristic of this magazine is that it is written in Jawi Malay which is the identity of the Pattani people. This descriptive qualitative research aims to analyze the existence of Azan magazine as an Islamic broadcast media. Data collection techniques were carried out using observation, interview, documentation and literature study. The data analysis technique uses Miles and Hubermen Interactive Analysis, with data validity techniques using the Triangulation method. The research results found that Azan magazine, which is now 50 years old, still exists as a medium for disseminating Islamic knowledge in Pattani, Thailand, and has become an identity for the Thai Muslim community.